Decoding Diversity: Indonesian Student’ Reception of Religious and Multicultural Themes in ‘Mentega Terbang’ Using Stuart Hall’s Encoding/Decoding Framework - Firly Annisa; Frizki Yulianti Nurnisya; Muhammad Raqib Bin Mohd Sofian; Elita Putri Pradipta; Eman M. Soliman (Universitas Ahmad Dahlan, 2026)
Non-Indexed Publication